Research Progress of Silicon based Micro Ring Resonators - HOU Linjun; FENG Song; OUYANG Jie; HU Xiangjian; LI Haojie; GUO Shaokai; LIU Yong; WANG Di; CHEN Menglin; FENG Lulu; ZHOU Ran; WU Jianyang; et al. (Guangtongxin yanjiu)
With the rapid growth of big data demand, electronic chips and their interconnection technologies cannot meet the requirements of high-speed data transmission and high energy efficiency in computing and storage systems. Compared to traditional electronic chips, Silicon based Photonic (SiP) integrated chips have lower costs, higher integration density, and larger communication capacity. Micro Ring Resonator (MRR), as an important optical device, has the advantages of high sensitivity, small size, and low power consumption, and is widely used in fields such as optical communication, optoelectronics, and sensors. MRR can be used for applications such as high-speed optical communication and optical signal processing. By injecting optical signals into the MRR, functions such as filtering, modulation, and amplification of optical signals can be achieved, thereby improving the transmission rate and reliability of optical communication. This article mainly summarizes the research progress of silicon based MRR at home and abroad from the perspectives of different structures and materials. It also analyzes the application limitations and performance effects of different structures on MRR, and compares the advantages and disadvantages of different materials in preparing MRR. The detailed horizontal and vertical comparison is made for the quality factor, free spectrum width, 3 dB bandwidth and other parameters that affect the device performance. This provides ideas for the further development of MRR photonic devices with higher integration and performance in the future.